Societal Adaptation to Coastal Tidal Flooding in Sayung Subdistrict, Demak Regency - Suhendra, M. Luthfi; Benardi, Andi Irwan (Jurnal Penelitian Geografi, 2025)
Tidal flooding (rob) along Pantura Road in Sayung District, Demak Regency has compelled local communities to adopt diverse adaptation strategies for survival. Using a descriptive qualitative approach with a case study design, this research explored coastal community adaptation strategies through observation, in-depth interviews, and document analysis. The findings reveal that adaptation varies according to economic capacity. Physical adaptations include raising house foundations, constructing multi-story buildings, and adopting stilt house designs. Socioeconomic adaptations involve collective action to remove road barriers, repurposing newly inundated pond areas, and diversifying livelihoods. Public facility adaptations are evident in the elevation of cemetery grounds and the modification of school infrastructure. Government interventions support these efforts through the development of pumping systems, construction of water barriers, and dredging of sedimentation channels. While tidal flooding reaching up to 40 cm disrupts daily community activities, it also creates new economic opportunities, particularly in fish cultivation. Overall, the study demonstrates that community adaptation is both dynamic and rooted in local wisdom, enabling resilience in the face of climate change impacts. These insights provide valuable contributions to understanding coastal community resilience and serve as references for adaptive management policies in similarly vulnerable coastal regions experiencing sea-level rise and recurrent tidal flooding.